Colour versus flavour in the choice of bread packaging design among children at Taman Asuhan & Didikan Kanak - Kanak University Malaya (Tadikum) Kuala Lumpur / Revathi Aruchunan - Revathi , Aruchunan (2019)
The key aspect of this study is to contribute to the Food & Beverages (F&B) industries, new marketing strategies personalized to young children as a customer. The purpose of this research is to examine young children as current customer, to evaluate the role of colour and its stimulus on final packaging colour choice of Tadikum children with regard to bread flavour represented by colour. This investigation was conducted in the mix method approached incorporating subject expert interview. Followed by, the experimental survey instrument was designed using EDDIE model and for analysis purpose, a cross-sectional analysis was employed and tested using SPSS software measured these results against the similar study conducted by scholars. In this study samples of 87 respondents from the age of four to six years old has been collected from Tadikum, Kuala Lumpur. The most preferred bread flavour among young children was found to play the greatest impact on packaging colour design clue then least preferred bread flavour. Conversely, investigator did not definite the influence of a demographic context in final flavoured bread packaging choice among respondent. This study definitively answers the researcher question regarding association between colour and bread flavour choice though packaging design among Tadikum children. Further studies are needed to establish causal relationships and develop preventative measures of multi-cultural aspect within Malaysia have more generalize judgements on child engaging product packaging for the Malaysia economic growth.